(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses one of the current issues in literary criticism today - the concept of philosophical-psychological interpretation and the task of this issue. The role and importance of artistic psychologism in literature is revealed through the story “The Green Lantern” by Alexander Green, a prominent representative of world literature.